Representation of women and pregnant women in HIV research: a limited systematic review. - Daniel Westreich; Molly Rosenberg; Sheree Schwartz; Geeta Swamy (PLoS ONE, 2013)
Background HIV-related outcomes may be affected by biological sex and by pregnancy. Including women in general and pregnant women in particular in HIV-related research is important for generalizability of findings. Objective To characterize representation of pregnant and non-pregnant women in HIV-related research conducted in general populations. Data sources All HIV-related articles published in fifteen journals from January to March of 2011. We selected the top five journals by 2010 impact factor, in internal medicine, infectious diseases, and HIV/AIDS. Study eligibility criteria HIV-related studies reporting original research on questions applicable to both men and women of reproductive age were considered; studies were excluded if they did not include individual-level patient data. Study appraisal and synthesis methods Articles were doubly reviewed and abstracted; discrepancies were resolved through consensus. We recorded proportion of female study participants, whether pregnant women were included or excluded, and other key factors. Results In total, 2014 articles were published during this period. After screening, 259 articles were included as original HIV-related research reporting individual-level data; of these, 226 were determined to be articles relevant to both men and women of reproductive age. In these articles, women were adequately represented within geographic region. The vast majority of published articles, 183/226 (81%), did not mention pregnancy (or related issues); still fewer included pregnant women (n=33), reported numbers of pregnant women (n=19), or analyzed using pregnancy status (n=9). Limitations Data were missing for some key variables, including pregnancy. The time period over which published works were evaluated was relatively short. Conclusions and implications of key findings The under-reporting and inattention to pregnancy in the HIV literature may reduce policy-makers' ability to set evidence-based policy around HIV/AIDS care for pregnant women and women of child-bearing age.